Extraction of Arthropods from Neotropical Soils with a Modified Kempson Apparatus - Adis, Joachim U. (Journal of Tropical Ecology, 2020)
A modified Kempson apparatus is described, the extraction procedure for arthropods in neotropical soils is given, and an example from Central Amazonia is presented. © 1987, Cambridge University Press. All rights reserved.